Dynamic of entangled pair of Rydberg atoms successively passing a thermal cavity - E.K. Bashkirov (Физика волновых процессов и радиотехнические системы, 2017)
In the present paper we invetigated the entanglement dynamics of two Rydberg atoms which are prepared in Bells type entngled state and succesively passing one-mode thermal cavity of one-atom maser. On the basis of exact solution we derived the Peres-Horodetskii parameter. We carried out the computer modeling of the entanglement for different model parameters.We shown that the thermal field can partially restored the initial entanglement.